The Struggle for Influence on the Roof of the World - E. M. Kozhokin (Vestnik MGIMO-Universiteta, 2022)
The key research task addressed in this article is to identify, using the example of Tajikistan, the main methods of struggle for influence currently used by leading international actors. Tajikistan is considered both as an autonomous actor with significant internal sources of development, and as an object of influence from more powerful states. The article analyses the nature of the actions taken by the United States, China, and Russia to gain political, economic, and cultural influence in this Central Asian republic. These states act as investors and trade partners in Tajikistan, they gain influence in education by promoting the study of English, Chinese and Russian languages. While the Western investments tend to decrease, the United States retains its influence, primarily in the financial sector. It also attracts the most active, young, educated citizens of Tajikistan to US for permanent residence. Of all countries, China has the most consistent and effective investment strategy, which includes the allocation of investment loans to Tajikistan, the creation of infrastructure facilities through these loans by Chinese companies and labor. The gradual establishment of China's dominance in the economic sphere is accompanied by an increase in China's presence in education and culture. Russia is Tajikistan’s main trading partner, the most important security provider, and destination for a critical number of labor migrants. There is a fundamental difference in the approaches of Russia, China, and the United States to Tajikistan: the activities of Russia and China are focused on maintaining and strengthening stability in Tajikistan, the United States, in the context of their campaign of tough confrontation with Russia, is ready to assist in destabilizing the situation in Tajikistan, using Islamists for this purpose.